INCREASING THE DEGREE OF GAS RECOVERY OF RESERVOIRS OF NATURAL GASES UNDER THE CONDITIONS OF THE MANIFESTATION OF THE WATER DRIVE USING CARBON DIOXIDE - Matkivsky, S. V.; Khaidarova, L. I. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2021)
To improve the existing technologies for field development under the conditions of the manifestation of a water drive, additional studies were carried out using the main tools of Eclipse and Petrel hydrodynamic modeling from Schlumberger. Based on the results of the studies carried out, it was found that in the presence of significant heterogeneity of productive reservoirs, it is necessary to ensure a high density of the injection wells network to effectively block the movement of formation water in comparison with the development of homogeneous reservoirs under the same conditions. This research result is explained by the advanced advance of the formation water front and non-hydrocarbon gases along the most highly permeable interlayers of the gas condensate field. Based on the results of the conducted studies, the maximum value of the number of injection wells for injecting carbon dioxide into homogeneous and heterogeneous reservoirs was determined in order to reduce the activity of the water pumping system and ensure stable operation of production wells for a long period of development of productive reservoirs. The maximum value of the number of injection wells at the time of the breakthrough of carbon dioxide in the production wells is 6.41 (6) wells for a homogeneous reservoir 7.74 (8) wells for a heterogeneous reservoir. The predicted gas recovery factor for the reduced maximum value of the number of injection wells in the homogeneous model is 65.05 %, and in the heterogeneous model - 55.56 %. When developing for depletion, the final gas recovery rates for homogeneous and heterogeneous models are 51.72 % and 49.44 %, respectively. The research results indicate the technological efficiency of introducing the technology of injection of carbon dioxide at the boundary of the initial gas-water contact in order to regulate the flow of formation water into gas-saturated horizons and increase the final gas recovery factor under such conditions.